Developing Comic Strip Media to Facilitate Students’ Reading Comprehension of Narrative Text - Kholidah, Diana; Hayuningtyas, Nina (Critical Review of English-Arabic World Journal, 2025)
The following difficulties have been reported to this study: students need media to facilitate their English learning, and uninteresting and dissatisfied classroom learning system. As a result, the study topic arising from these issues is the creation of comic strip media when combined with liveworksheet.com. The objective of this research is to describe the designing and developing multimedia learning using comic strip in narrative text for first grade students of Senior High School. The Design and Develop Research approach was employed in this study, which included planning, designing, developing, and validating. The trial subjects in the study included content expert, media expert, and English teacher of MA. Sunan AmDesign, Comic Strip Media, Reading Comprehension, Narrative Textpel. Observation, interviews, documentation, and validation sheets (from content expert, media experts, and English teachers) were employed as instruments. The average result reached for the design and development of learning media regarding comic strip media based on validation sheets from content experts, media experts, and English teachers is 89% (very high). As a result, it can be stated that the design and development of learning media for narrative text with reading comprehension abilities, particularly for tenth grade students, is extremely high to be employed in English language learning in the classroom.